Systematic Literature Review: Pengaruh Model Pembelajaran Make a Match pada Hasil Belajar Matematika - Sesilia Novitry Tafonao; Yuni Sara Silaban; Siti Salwa Arianto; Lidya Tumanggor (Journal on Education, 2025)
Mathematics is a basic subject that plays a crucial role in improving the quality of education and honing logical and systematic reasoning skills. However, some students often find the mathematics learning process monotonous, necessitating a more creative and engaging approach. One relevant approach is the Make-A-Match learning model, a method that combines paired card games to build knowledge through interaction and collaboration between students. This model has proven effective in improving learning outcomes, creating a fun learning environment, and encouraging student engagement at every stage of learning. In this regard, teachers play a crucial role in creating a conducive and enjoyable learning environment, while adapting learning strategies to students' needs and development. Therefore, using the Make-A-Match model can be an appropriate alternative to optimize the achievement of mathematics learning objectives.